Analisis Kemampuan Representasi Dalam Pemecahan Masalah Matematika Ditinjau Dari Gaya Belajar Siswa (Universitas Muhammadiyah Purworejo, 2023)
This study aims to analyze the representation abilities of SMP IT Permata Bunda Islamic Boarding School Bandar Lampung students in terms of their learning styles. This study uses a qualitative method with a descriptive approach. Data collection was carried out by means of a learning style questionnaire, written tests, and interviews. The subjects to be observed were carried out through a purposive sampling technique so that 6 students in class IX were obtained, each of whom had a visual learning style, auditory learning style, and kinesthetic learning style which would then be analyzed using technical triangulation based on the results of representational ability tests and interviews to draw conclusions. of this study to answer the formulation of the problem. The data will be arranged sequentially using data analysis techniques carried out through three stages, namely data reduction, data presentation and drawing conclusions/verification. The analysis was developed based on indicators of representational ability by taking into account the learning styles of students. Based on the results of the study, it can be concluded that students with a dominant visual learning style with visual representation abilities, students with a dominant auditory learning style with verbal representation abilities, and students with a kinesthetic learning style are more dominant with their visual representation abilities.